Estudo de uma proposta didática sociointeracionista para abordar astronomia no sexto ano do ensino fundamental - Silva, Barbara Locatelli da (2019)
The study arises from the need to develop didactic proposals to approach topics related to Astronomy in Elementary School through theorical perspectives that prioritize social relations and favor the building of concepts inside a dialectical process. Such identification led of the following question as the central questioning of the study: which elements are favored in a social interactionist pedagogical practice? From it, it is aimed to analyze the potentialities of a teaching guided by the social interactionist perspective to approach topics of Astronomy in Elementary School level. As theorical reference, the study seeks for subsidy in social interactionism, particularly in the perspective of Lev Semenovich Vigotski. Such assumptions lead to the creation of a didactic sequence based on the use of questions and involving different didactic resources as movies, games and experimental activities, in a way to provide interaction, dialogue and participation of the students. The application of this didactic sequence took place in a six-year-class at a state public school in Rio Grande do Sul. The investigation was of qualitative and participative nature, presenting as data collection instruments, the board diary filled out by the researcher. The discussion of these data had as reference the processes of social interaction and were supported in the theorical reference elaborated for the study. As analysis categories, it was possible to identify from the selected theory aspects like interaction student/student, student/teacher and student/material. The study results point out to the first category where students could fully interact with their peers, making communication and dialogue possible towards sharing and knowledge building; in the second category, records of the board diary showed that the students had the opportunity and freedom to interact with the teacher/researcher in a way to ask questions and make comments that enriched their learning process; and the third category showed the importance of using didactic material regarding the reality of each class, bringing elements that enable their interaction in a way to recover their acquired knowledge spontaneously and contextualized with their culture. The educational product that follows the study refers to the created didactic sequence and it is available in the form of support material to teachers on the program website and Portal Educapes (http://educapes.capes.gov.br/handle/capes/431744).